BIOFLOKULASI MIKROORGANISME DAN PERANANNYA DALAM PENGOLAHAN AIR LIMBAH SECARA BIOLOGI - Milono Poesponegoro (Jurnal Kimia Terapan Indonesia, 1998)
Bioflocculation is a direct result of the ability of the microorganims to agglomerate into large flocs with a high settling velocity, and is an important phenomenon often encountered in the biological treatment of wastewater. Bioflocculation is also very important in determining the dewatering characteristics of a sludge.The key 10 the successful operation of biological-oxidation units is the maintenance of adequate nutrients, microorganisms, and a favourable environment for the organisms to grow and utilize the organic matter. Although algae, bacteria, fungi and protozoa are introduced into the activated sludge, bacteria usually dominant as the primary feeders on the organic waste. The dominant bacteria of the sludge must satisfy two conditions: they must be able to utilize the organic waste and also be capable of readily forming flocs to facilitate separation from eflluent and thereby ensure their retention in the system. Therefore, it is essential to ensure that the proper environment is produced and effectively controlled to pave the dominant growth of flocforming bacteria in the system so that the settling characteristics of the sludge obtained are good.Flocculation of discrete microbial cells can either be biologically (bioflocoulation) or chemically induced (chemical flocculation). There seems to be general agreement that bioflocculation of microorganisms was observed to follow mechanism similar to those observed in the chemical flocculation of microorganisms. A review on the bioflocculation of microorganisms in relationship to aerobic wastewater treatment proces and to cultural and microbial growth conditions is presented. The bioflocculation mechanism is also discussed and summarized.